Description of bone mineral density in postmenopausal women at Immunoendocrinology Integrated Laboratory, Faculty of Medicine University of Indonesia (Faculty of Medicine Universitas Indonesia, 2004)
To identify the pattern of bone mineral density in postmenopausal women through retrospective study in 40 postmenopausal women using Dexa instrument in bones (L2 - L4). Results with 15% of survey formula accuracy were found: mean of menopausal age was 53.25 years, normal bone mineral density 30%, osteopenia 52.5%, and osteoporosis 17.5%. A very strong relationship (r=0.547) and a significant relationship (p=0.000) between body height and bone mineral density were found in this study, and there was a moderate (r=0.315) and significant (p= 0.047) relationship between body weight and bone mineral density, and likewise there was a moderate (r=-0.301) and significant (p=0.059) relationship between duration of menopause and bone mineral density. By contrast, no relationship was found between age (r=0.119) and Body Mass Index (BMI) (r=0.086) and bone mineral density. (Med J Indones 2004; 13: 31-9)Keywords: Duration of menopause, menopause age, body height, body weight, body mass index, and bone mass density